2019
DOI: 10.1186/s13717-019-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil and water conservation practices on soil physicochemical properties in Gumara watershed, Upper Blue Nile Basin, Ethiopia

Abstract: Background: Soil erosion is among the foremost causes of declining soil resources in Ethiopia, which in turn affect agricultural productivity. To limit this problem, for the last two decades in Gumara watershed, soil and water conservation measures have been practiced through free labor community mass-mobilization. However, their effect on soil fertility has not been evaluated. This study investigated the impact of implemented soil and water conservation measures on fertility improvement in the Gumara watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 40 publications
26
58
2
Order By: Relevance
“…The result is consistent with the finding of Bekele et al (2019) in the Karesa watershed south west Ethiopia who found a comparable result ranging from 0 to 25 ton/ha/year. The finding was also consistent with the finding of Belayneh et al (2019), who estimated the annual soil loss ranges from 0.01 to 442.92 ton/ha/year. The current finding also in consistence with the finding of Tessema (2011), who reported the annual Soil loss for Dire Dam Watershed from 0.00 to 263.25 ton/ ha/year, Amsalu and Mengaw(2014), reported the annual soil loss in Jabi Tehinan Woreda ranges from nearly 0 in south and central parts of the area to 504.6 ton/ha/year in steeply sloping mountainous areas of the north and northeastern parts of the catchments.…”
Section: Discussionsupporting
confidence: 92%
“…The result is consistent with the finding of Bekele et al (2019) in the Karesa watershed south west Ethiopia who found a comparable result ranging from 0 to 25 ton/ha/year. The finding was also consistent with the finding of Belayneh et al (2019), who estimated the annual soil loss ranges from 0.01 to 442.92 ton/ha/year. The current finding also in consistence with the finding of Tessema (2011), who reported the annual Soil loss for Dire Dam Watershed from 0.00 to 263.25 ton/ ha/year, Amsalu and Mengaw(2014), reported the annual soil loss in Jabi Tehinan Woreda ranges from nearly 0 in south and central parts of the area to 504.6 ton/ha/year in steeply sloping mountainous areas of the north and northeastern parts of the catchments.…”
Section: Discussionsupporting
confidence: 92%
“…Haplic alisols cover the dominant portion (43.76%) of the watershed. The soil in the area is characterized by heavy clay content on average approximately 65% (Belayneh et al 2019b). The dominancy of clay soils than sand and silts can cause high runoff and sediment loss (Bashari et al ).…”
Section: Study Areamentioning
confidence: 99%
“…Currently nearly, 90% of the local population relies on subsistence based agricultural activities with a population density of over 185 persons per square kilometer. This might be the case that the soil in the Gumara watershed is characterized by low organic carbon and total nitrogen contents (Belayneh et al 2019b).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In 1970s various soil and water conservation measures have been implemented by Ministry of Agriculture in Ethiopia [15, 16, 17, 18 19]. Since then, many efforts were given to conserve the natural resources under watershed management [19]. There are success stories of watershed management in many districts of Ethiopia [8,14,20,21].…”
Section: Introductionmentioning
confidence: 99%